Kontseptsiya blokovoj kompozitsii v podgotovke sportsmenov vysokogo klassa - Issurin, V. G.; Shklyar, V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The purpose of this research was the generalization and the critical judgment of the basic aspects of modern training construction for elite athletes: 1) the total volumes and limits of training loads; 2) the block composition as the concept of modern planning; 3) the leading to the main competitions of a season. The following sources of the information were involved in the publication: the experience of the training of the leading Soviet athletes during 1976-1991; the experience of the training of combined teams of Israel 1992-2001; the materials of the world scientific press and direct dialogue with the experts of the different countries; the own substantial, statistical and logic analyses. The positions presented in the article concern to the training in individual kinds of sports that does not exclude their critical adaptation for sports games. Some elements of the substantiation presented in the article remain little-known, however the concept of block construction was used in sports of the maximum achievements for a long time. The experience of its realization in the endurance kind of sports shows an opportunity for essential reducing of superfluous volumes of total training work that corresponds to the general tendency of the last years.